Two new records of puffballs in Thailand - Jaturong Kumla (2018)
Calvatia holothurioides and Morganella puiggarii, two puffballs in the Agaricaceae, are reported for the first time from Thailand. The specimens were identified based on morphological and ITS sequence analyses. Descriptions and illustrations are provided.